Artemisia scoparia and Metabolic Health: Untapped Potential of an Ancient Remedy for Modern Use - Boudreau, Anik; Richard, Allison J.; Harvey, Innocence; Stephens, Jacqueline M. (Frontiers in Endocrinology, 2022)
Botanicals have a long history of medicinal use for a multitude of ailments, and many modern pharmaceuticals were originally isolated from plants or derived from phytochemicals. Among these, artemisinin, first isolated from Artemisia annua, is the foundation for standard anti-malarial therapies. Plants of the genus Artemisia are among the most common herbal remedies across Asia and Central Europe. The species Artemisia scoparia (SCOPA) is widely used in traditional folk medicine for various liver diseases and inflammatory conditions, as well as for infections, fever, pain, cancer, and diabetes. Modern in vivo and in vitro studies have now investigated SCOPA’s effects on these pathologies and its ability to mitigate hepatotoxicity, oxidative stress, obesity, diabetes, and other disease states. This review focuses on the effects of SCOPA that are particularly relevant to metabolic health. Indeed, in recent years, an ethanolic extract of SCOPA has been shown to enhance differentiation of cultured adipocytes and to share some properties of thiazolidinediones (TZDs), a class of insulin-sensitizing agonists of the adipogenic transcription factor PPAR. In a mouse model of diet-induced obesity, SCOPA diet supplementation lowered fasting insulin and glucose levels, while inducing metabolically favorable changes in adipose tissue and liver. These observations are consistent with many lines of evidence from various tissues and cell types known to contribute to metabolic homeostasis, including immune cells, hepatocytes, and pancreatic beta-cells. Compounds belonging to several classes of phytochemicals have been implicated in these effects, and we provide an overview of these bioactives. The ongoing global epidemics of obesity and metabolic disease clearly require novel therapeutic approaches. While the mechanisms involved in SCOPA’s effects on metabolic, anti-inflammatory, and oxidative stress pathways are not fully characterized, current data support further investigation of this plant and its bioactives as potential therapeutic agents in obesity-related metabolic dysfunction and many other conditions.